Impact of the COVID-19 pandemic on the non-cancer chronic pain and its management in the elderly - Pereira,Joana Isabel Aparício (2022)
ABSTRACT BACKGROUND AND OBJECTIVES: Chronic non-cancer pain is considered a public health problem, affecting 37% of the Portuguese population. Pain treatment represents a fundamental human right. However, during the COVID-19 pandemic, the vast majority of these patient care services were considered non-urgent or non-emergent, and clinical appointments and treatment were postponed or un-scheduled. Imposed restrictions, such as measures to prevent a COVID-19 infection, became counterproductive with regard to the management of chronic pain. Its impact should be emphasized especially in the older population, due to the associated physical and psychological comorbidities. This study aimed to analyze the impact of the COVID-19 pandemic on the pain of older people in four aspects: i) intensity, treatment and management of pain; ii) mental health; iii) lifestyles; iv) quality of life. METHODS: Review in Pubmed, SCOPUS and SCIELO databases using the terms: chronic non-cancer pain, pain management, aged and COVID-19. 86 articles were found and 13 were selected. Articles included cumulatively addressed chronic pain, represented original research of a clinical nature, and analyzed the impact of the COVID-19 pandemic on the management of chronic pain. Preference was given to studies with participants aged 65 years or older. Studies in adults with no mention of age in the context of the COVID-19 pandemic impact on aspects infuencing chronic pain and its management were also included. Only one article exclusively studied the senior population. RESULTS: The pandemic affected: i) increased pain intensity (n=10), changes in its pharmacological and non-pharmacological treatment (n=3) and its management, that is, the adaption of the health professionals and patients (n=1); ii) negatively affected mental health: symptoms of stress and anxiety/depression (n=9), psychological distress (n=4), social isolation/loneliness (n=6); iii) lifestyles: physical activity (n=4), sleep quality (n=4) and physical performance (n=5); iv) reduction of quality of life (n=5). Despite the heterogeneous results, a worsening of pain and mental health was found, as well as alteration of styles and quality of life and disruption of medical services. CONCLUSION: The restrictions imposed by the pandemic affected several areas of pain in the short term. Telemedicine has emerged as an adopted solution, but the barriers in the senior population, such as lack of digital literacy and lack of technological equipment, cannot be overlooked. The lack of knowledge of the specific impact of COVID-19 on the pain of the senior population calls for more research that focuses on the long-term consequences, as well as the solutions to be adopted in order to contain the damage in this vulnerable population. HIGHLIGHTS Worsening of pain and mental health, change in lifestyles and decreased quality of life. Disruption of medical services generated by the pandemic period reinforce the need for a holistic and individual approach to health care. Impact of the pandemic on chronic pain management has been little explored in older people. Need for further research focusing on long-term consequences, as well as the solutions to be adopted in order to contain injuries or dysfunctions in this vulnerable population.